Proximate, Mineral and Fatty Acid Composition of Catla catla Reared in Fresh Water and Waste Water Environment - Paul, Baidya Nath; Mandal, Rathindra Nath; Chakrabarti, Partha Pratim; Adhikari, Subhendu; Pandey, Bijay Kumar; Singh, Puja; Bhowmick, Sadrupa (Indian Journal of Animal Nutrition, 2018)
The study was carried out to determine the differences in proximate, mineral and fatty acid composition of Catla catla reared in freshwater (FW) and wastewater (WW). The samples were collected from different places of West Bengal and the weight ranges from 250-2500g. Crude lipid, total ash and the moisture content did differ significantly between the two groups. However, protein content was significantly higher (P<0.05) in WW reared catla. Zinc and selenium content was significantly (P<0.05) higher in WW reared catla. 0.40±0.09 and 0.75±0.07 zinc content was present in FW and WW reared catla respectively. However, iron, manganese, sodium, potassium and calcium content was non-significant for the groups. 63.21±1.41 and 67.73±3.78 content of saturated fatty acid was respectively present in FW and WW reared catla. Palmitic acid was predominant SFA in both the groups. Myristic acid and heneicosanoic acid content was significantly (P<0.05) higher in FW reared catla. Whereas, stearic acid was significantly (P<0.05) higher in WW reared catla. Monounsaturated fatty acid (MUFA) content was 18.32±1.01 and 17.97±0.62 respectively in FW and WW reared catla. Among MUFA, oleic acid content was significantly (P<0.05) higher in FW reared catla. The polyunsaturated fatty acid (PUFA) content was 18.47±2.13 and 14.3±1.47 respectively in FW and WW reared catla. Among PUFA, eicosapentanoic acid (EPA) and docosahexanoic acid (DHA) content were 3.01±0.83 and 1.98±0.15; 0.52±0.09 and 0.21±0.04 respectively in FW and WW reared catla. Conclusive results from the analyzed samples were presented in this study that the proximate, mineral and fatty acid composition were similar in both the reared catla.